PERBEDAAN KIPI PADA PEMBERIAN PARASETAMOL SEBELUM DAN SESUDAH IMUNISASI PENTABIO DI WILAYAH PUSKESMAS WONOSARI - Ratna Suparwati; Hartijah Kartini; Syska Atik (Jurnal Kesehatan dr. Soebandi, 2018)
Abstract : Immunization is an attempt to provide immunity to infants and children by entering the vaccine into the body to make the body anti-substance to prevent certain diseases. The purpose of immunization is to stimulate the body's immunological system to form a specific antibody so as to protect the body from the attack that can be prevented by immunization (PD3I). Factors causing no UCI include Drop Out immunization occurrence, such as lack of knowledge of mother about immunization, pamong involvement in motivating mother. Pentabio post-immunization (KIPI) incident became one of the factors that did not reach UCI Coverage. The purpose of this study was to know the difference of KIPI in giving paracetamol before and after Pentabio immunization. Comparative Analytic Research Design with Prospective approach, with the population of 86 babies aged 2,3,4 months, Sampling using Simple Random Sampling technique with the number of samples as much as 70 respondents of baby age 2,3,4 months that fulfill inclusion criteria. The research instrument uses Kuisuener which contains general data and special data. The results of this study using Chi Square formula which shows that there are differences in KIPI on administration of paracetamol before and after immunization Pentabio. Based on the results of the above study, should be a reference for health workers to apply paracetamol 30 minutes before immunization pentabio